Rethinking China's local government debt in the frame of modern money theory - Zengping He; Genliang Jia (Levy Economics Institute of Bard College, 2019)
Local government debt in China is increasing and presents a great threat to China's financial stability. In China's fiscal system, the central government often prioritizes reducing its fiscal deficit and can determine to a great extent the distribution of revenue and expenditure between itself and local governments. There is therefore a tendency for the fiscal burden to be shifted from the central government to the local governments. Resolving China's local government debt problem requires not only strengthening regulation, but also abandoning the central government's fiscal balance target, because this target may make regulation hard to sustain in times of economic downturn. This paper discusses central-local fiscal relations in the framework of Modern Money Theory, suggesting that, because a government with currency sovereignty can always afford any spending denominated in its own currency, China's central government should bear a greater fiscal burden.
Keywords: G18; H74; H77; O53; 330; Local Government Debt; China; Modern Money Theory; Fiscal Systems